Maracatu à paraibana : uma análise das reinvenções e conexões político-sociais-religiosas a partir do Pé de Elefante - Negreiros, Regina Coeli Araújo (2018)
This work has the general objective of analyzing the Maracatu Pé de Elefante, as the only maracatu nation of Paraíba in the present day, and to understand its relation with the terreiro Ilê Axé Xangô Ogodô and Tenda do Caboclo Sete Flechas, problematizing and analyzing the question of the categories of Maracatus de Baque-turned, ie, "maracatus nation" and "batuques or maracatus laicos," and the line separating these categories, given the controversies they generate in the context of Afro-Brazilian religions, besides observing the political-socialreligious connections of the Elephant Foot and its constant reinvention and resignification in the set of maracatus in Paraíba. As specific objectives, we seek to consider, in a first moment, the origins of Maracatu as a religious manifestation coming from the terreiros from the African diaspora and its propagation as a cultural manifestation and as musical language that spills out of the terreiros. Later, we took as an object of analysis the Maracatu Elephant Foot, which in 2018 completed its ten years of existence and which is located in the field of the marquee of threshing and seated in the terreiro Ilê Axé Xangô Ogodô and Tenda do Caboclo Sete Flechas. For that, it became necessary to understand the history and the place of the said terreiro, as well as the trajectory of his religious leadership, Father Beto de Xangô. From this trajectory, we analyze, at the end, the reinvention and the re-signification of the tradition from the Foot of Elephant, drawing a parallel with the other turned bumps present in the state of Paraíba, with the perspective of dimensioning the border zone between them in what concerns the religious question and the community activities within a context where cultural hybridization anchors and restructures structures, cultural and social practices, thus situating the Elephant Foot in the category of Maracatu Nation, given its insertion in what concerns the ethos and the religious ethos. The theoretical-methodological perspective that guides the work is ethnographic, comprising ethnography not only as a method of investigation, but also as a theoretical perspective. In this way, this research is placed in the field of the Sciences of Religions in the field of "empirical studies of religion", particularly in dialogue with the Anthropology of Religions. We use specialized anthropological literature for this purpose, as well as recovering folklorists who treated the subject in a pioneering way. We also emphasize that the research presents a strong contribution to the area of Religious Sciences, which still has few studies on this subject, as well as for the field of Afro-Brazilian studies, in which the dimension of musicality still shows itself as an aspect research. It is also relevant from the point of view of regional history, since unlike Pernambuco, a neighboring state where maracatus are the object of several studies, in Paraíba the subject has not yet been properly explored.